Notes on Vampyressa thyone (Chiroptera: Phyllostomidae): distribution, genetics and hypopigmentation - Hernández-Canchola, Giovani; Gómez-Jiménez, Yire A.; Hernández-Chávez, Iván; Lucero-Verdugo, Sara Carolina; León-Paniagua, Livia (Biota Neotropica, 2019)
Abstract: The frugivorous bats of the genus Vampyressa include five neotropical species, and some of them are considered relatively rare and uncommonly encountered. The northernmost distribution of this genus is in Mexico where only one species, the monotypic Vampyressa thyone, is found. Here, we report the Northwesternmost record for this species, extending its distribution range to the state of Guerrero, Mexico. This record extends the limit of the species distribution by more than 153 km. We also compared this specimens with other V. thyone, and using mitochondrial cytochrome-b sequences we detected three geographic clades within the species. The new Mexican specimen represent the most divergent cytochrome-b sequence within V. thyone. We recommend a taxonomic revision to validate the taxonomic status of the three groups detected within V. thyone, particularly the differentiated Mexican clade. Additionally, we report a case of hypopigmentation in another V. thyone collected in a mature tropical rainforest in Chiapas, Mexico.